Radio frequency energy inactivates peroxidase in stem lettuce at different heating rates and associate changes in physiochemical properties and cell morphology. (16th April 2021) - Yao, Yishun; Sun, Yanan; Cui, Baozhong; Fu, Hongfei; Chen, Xiangwei; Wang, Yunyang
Highlights: Faster RF heating rate improved peroxidase inactivating efficiency. Damage to the microstructure deteriorated the physiochemical properties. The degrees of cell destruction varied with RF heating rates. Different RF heating rates suit for producing different types products. Abstract: Radio frequency (RF) is an emerging technology applied in blanching treatment as alternative to conventional treatment. This study aimed to investigate the effects of RF heating rate on peroxidase (POD) inactivating efficiency, physiochemical properties (texture, color and vitamin C) and cell structure of stem lettuce. POD enzyme inactivation efficiency increased with increased RF heating rate. When POD activity was reduced to <5%, better physiochemical properties and less cell damage occurred in RF heating compared with conventional hot water (HW) blanching (HWB); Relative electrolyte leakage (REL) analysis and microscopic observation suggested that the loss of integrity of cell walls and membranes, the decrease in turgor pressure and the weakened connections between adjacent cells leaded to the deterioration of physiochemical properties. The degrees of cell destruction varied with RF heating rates, which provide a new idea for RF blanching for producing different types of fruits and vegetables products (Solid and juice products).